The variability of glycated hemoglobin is associated with renal function decline in patients with type 2 diabetes - Chia-Lin Lee; Cheng-Hsu Chen; Ming-Ju Wu; Shang-Feng Tsai (SAGE Publishing, 2020)
Background: The effect of glucose control, especially variability of glycated hemoglobin (HbA1c), on estimated glomerular filtration rate (eGFR) decline in type 2 diabetes is still debatable. Methods: We used tertiles of coefficient of variation (CV) to determine the variability of HbA1c (HbA1c_CV). Mixed model repeated measures (MMRM) were used to evaluate the annual eGFR decline rate. Results: In 1383 type 2 diabetic patients, we found the greater the HbA1c_CV, the greater the eGFR decline ( p  = 0.01, −0.99 in low, −1.73 in mid, and −2.53 ml/min/1.73 m 2 /year in high HbA1c_CV). Regardless of eGFR (⩾60 or <60 ml/min/1.73 m 2 ), the same result holds ( p  = 0.019 and p  = 0.007, respectively). In subgroup analysis of baseline HbA1c (%) (HbA1c < 7, 7 ⩽ HbA1c < 9, and HbA1c ⩾ 9), tertiles of HbA1c_CV showed similar effects on annual decline of eGFR ( p  = 0.193, 0.300, 0.182, respectively), although a trend for a steeper decline in renal function in the highest HbA1c_CV tertile was observed for all HbA1c strata, and even for HbA1c < 7%. A similar behavior was observed in patients with macroalbuminuria or normoalbuminuria ( p  = 0.219, and 0.109, respectively), with a significant trend in those with microalbuminuria ( p  = 0.019). Even in patients with HbA1c < 7, high HbA1c_CV also predicts rapid eGFR decline. Before macroalbuminuria, minimizing HbA1c_CV also has renal benefit. Conclusions: HbA1c variability is an independent risk factor for deterioration of renal function. Even with well-controlled HbA1c levels (<7%), patients with high HbA1c_CV still experienced faster eGFR decline. Early minimization of glycemic variability (before macroalbuminuira) can curb deterioration of renal function. Monitoring and lowering of HbA1c_CV is highly recommended for diabetic care.